Diuron and its metabolites induce mitochondrial dysfunction-mediated cytotoxicity in urothelial cells - Lima, Thania Rios Rossi [UNESP]; Kohori, Natalia Akemi [UNESP]; de Camargo, João Lauro Viana [UNESP]; da Silva, Carla Adriene [UNESP]; Pereira, Lilian Cristina [UNESP] (Taylor & Francis, 2024)
In the environment, or during mammalian metabolism, the diuron herbicide (3-(3,4-dichlorophenyl)-1,1-dimethylurea) is transformed mainly into 3-(3,4-dichlorophenyl)-1-methylurea (DCPMU) and 3,4-dichloroaniline (DCA). Previous research suggests that such substances are toxic to the urothelium of Wistar rats where, under specific exposure conditions, they may induce urothelial cell degeneration, necrosis, hyperplasia, and eventually tumors. However, the intimate mechanisms of action associated with such chemical toxicity are not fully understood. In this context, the purpose of the current in vitro study was to analyze the underlying mechanisms involved in the urothelial toxicity of those chemicals, addressing cell death and the possible role of mitochondrial dysfunction. Thus, human 1T1 urothelial cells were exposed to six different concentrations of diuron, DCA, and DCPMU, ranging from 0.5 to 500 µM. The results showed that tested chemicals induced oxidative stress and mitochondrial damage, cell cycle instability, and cell death, which were more expressive at the higher concentrations of the metabolites. These data corroborate previous studies from this laboratory and, collectively, suggest mitochondrial dysfunction as an initiating event triggering urothelial cell degeneration and death.
Keywords: 1T1 cell culture; diuron and metabolites; mitochondrial pathways; Mitotoxicants; toxicodynamics